Project on Human Development in Chicago Neighborhoods (PHDCN): Young Adult Self Report, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2006)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One of the measures that composed the Longitudinal Cohort Study was the Young Adult Self Report (YASR). The YASR protocol was first developed by Thomas M. Achenbach. It has been a widely used measure for evaluating subjects between the ages of 18 and 30 with respect to their functioning in social relationships, level of mental, emotional and physical health, substance use and abuse, and their tendencies toward antisocial and criminal behavior. The Wave 3 PHDCN version of the Young Adult Self Report offered a thorough self-assessment of the respondents belonging to Cohorts 15 and 18 of the Longitudinal Cohort Study. The Wave 3 instrument featured a reduced version than was used in Wave 2 (PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): YOUNG ADULT SELF REPORT, WAVE 2, 1997-2000 [ICPSR 13666]).